Measurements of bowel microdialysis recovery with an online biosensor system - Corcoles,EP; Deeba,S; Hanna,GB; Boutelle,MG; Darzi,A (Proceedings International Conference on Instrumentation Communication Information Technology and Biomedical Engineering 2011 Icici Bme 2011, 2011)
Microdialysis is a sampling technique based on the passive diffusion of the molecules through a small segment of cylindrical hollow fiber membrane implanted within the tissue of study. Calibration of the microdialysis probe and the parameters that affect this calibration are essential, since recovery factors are never 100%. In vitro calibration methods are typically used to compare the concentration of the outlet with the concentration of the medium. In vivo quantification methods of microdialysis data monitoring depends on active and passive tissue effects, complicating the calibration methods further. In vitro and in vivo microdialysis calibration methods were performed in gastrointestinal tissue of animal models and intensive care patients. Results showed that the discrepancy between in vitro and in vivo calibration method is minimal. © 2011 IEEE.